Prognosis and predictive value of heat-shock proteins expression in oral cancer: A PRISMA-compliant meta-analysis. Issue 3 (22nd January 2021) - Lu, Wei; Wang, Yongwu; Gan, Min; Duan, Qingyun
Abstract: Background: Heat-shock proteins (HSP) is a key chaperone protein which maintains intracellular proteostasis and is expressed on the surface of solid and hematological malignancies. Several studies have reported paradoxical evidence of the association between HSP expression and prognosis of oral cancer. To address the discrepancy, we carried out the meta-analysis to assess the role of HSP such as: HSP70, HSP90, HSP27, HSP60, and HSP105 in susceptibility, progression, and prognosis of oral cancer. Materials and methods: We retrieved the PubMed, Embase, Web of science, China National Knowledge Infrastructure (CNKI), and Wanfang databases to acquire the eligible studies which were associated with HSP70, HSP90, HSP27, HSP60, and HSP105 protein expression and oral cancer. We applied hazard ratio (HR) and its 95% confidence interval (95% CI) to assess the value of HSP protein expression in overall survival of oral cancer; odds ratio (OR) and its 95% CI were used to evaluate the association of risk and clinical features of oral cancer. Funnel plot, Begg test, and Egger line regression test were utilized to observe publication bias among studies. All statistical analysis was performed with Stata 14.0 software (Stata Corporation, College Station, TX). Results: A total of 26 studies were included in the present meta-analysis. On based of the results, HSP70 and HSP27 had no significant association with progression of oral cancer. However, the pooled HR and 95% CI revealed a significant well effects of HSP70 and HSP27 expression on survival of oral cancer. Moreover, the susceptibility of oral cancer was significantly associated with HSP70 and HSP60 overexpression. Conclusion: HSP70 and HSP27 protein overexpression might be valuable biomarkers for the prognosis of oral cancer. And HSP70 and HSP60 might have potential predictive effects on the risk of oral cancer.